Rex: Symbolic Regular Expression Explorer - Veanes, Margus; Halleux, Jonathan "Peli" de; Tillmann, Nikolai (Third International Conference on Software Testing, Verification and Validation (ICST), 2010)
Constraints in form regular expressions over strings are ubiquitous. They occur often in programming languages like Perl and C#, in SQL in form of LIKE expressions, and in web applications. Providing support for regular expression constraints in program analysis and testing has several useful applications. We introduce a method and a tool called Rex, for symbolically expressing and analyzing regular expression constraints. Rex is implemented using the SMT solver Z3, and we provide experimental evaluation of Rex.